A new species of Anacroneuria Klapálek, 1909 (Plecoptera: Perlidae) from Selva Lacandona, Mexico. Issue 3 (3rd July 2019) - Mayorga, Alfredo; Barba-Alvarez, Rafael
Abstract: A new species, Anacroneuria lacandona sp. n., from Reserva de la Biosfera Montes Azules, Selva Lacandona, in Mexico, is described and illustrated. A provisional key to males of Mexican species of Anacroneuria Klapalek, 1909 is provided. It is based on the key by Stark and Kondratieff (2004 ) and is updated by including the recently described species. http://zoobank.org/urn:lsid:zoobank.org:pub:76735B1B-219A-4DC8-8BB3-B628CA11C5CB